A preparation method of a titanium-based lithium ion sieve, a product prepared therefrom and applications
Patent Information
- Application Number
- CN202310679048.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-08
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-06-08
AI Technical Summary
[0008]本发明的目的之一在于提供一种钛基锂离子筛的制备方法,解决现有技术混料不均匀、干燥过程中物料重新分离的问题;解决烧结过程的烧结工艺不当而出现的产品性能偏低的问题
(1)本发明利用水溶性的锂源代替水不溶性碳酸锂作为锂源,和水不溶性的二氧化钛进行混合,水溶性的柠檬酸锂将浸润并包裹在二氧化钛的表面,可以使锂源和钛源混合的更加充分,在反应过程中减少锂离子的迁移路程,提高反应速率;
Smart Images

Figure CN116692933B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion adsorption technology, and in particular to a method for preparing a titanium-based lithium-ion sieve, the products obtained therefrom, and their applications. Background Technology
[0002] In recent years, with the development of new lithium adsorbents and extractants, as well as the application of membrane technology, my country's lithium extraction technology from salt lakes has developed rapidly. Currently, the main technology for lithium extraction from salt lakes in China is the composite technology of lithium adsorbents and membranes, and breakthroughs in lithium adsorbent technology are crucial.
[0003] Currently, the synthesis of titanium-based lithium-ion sieves mainly employs the high-temperature solid-state method. This method is simple, easy to operate, and readily scalable. The synthesis of titanium-based lithium-ion sieves using the high-temperature solid-state method requires steps including "mixing of lithium and titanium sources," "material drying," "intermediate material crushing," "high-temperature calcination," and "finished product crushing." These steps are prone to problems such as uneven mixing, material re-separation during drying, and improper sintering processes, leading to inconsistent and low-quality titanium-based lithium-ion sieve products.
[0004] CN115069209A discloses a titanium-based lithium-ion sieve inorganic composite adsorption lithium extraction material and its preparation method. The method involves mixing a titanium-based lithium-ion sieve or its precursor with a regulator, a curing agent, and a resin monomer. The polymer monomer undergoes a polymerization reaction at a specific temperature and gradually solidifies. During this process, granular materials of a specific shape are prepared by extrusion or spray drying. Then, the mixture is calcined at high temperature under anaerobic conditions and acid-treated to obtain a carbon-supported titanium-based lithium-ion sieve inorganic / inorganic composite lithium extraction material.
[0005] CN114345291A discloses a method for preparing a high-adsorption-capacity granular titanium-based lithium-ion sieve adsorbent. The method includes step 1, preparing titanium-based lithium-ion sieve precursor powder; and step 2, preparing the high-adsorption-capacity granular titanium-based lithium-ion sieve adsorbent, comprising: 1) pretreatment of the precursor powder; 2) preparation of the composite adhesive; 3) doping, blending, and homogenization; 4) granulation; and 5) elution and displacement. This granular adsorbent has high porosity and exhibits good suspension properties, fast adsorption / desorption rates, and high lithium extraction activity when extracting lithium from salt lake brine or simulated brine. However, the lithium source in this patent is lithium carbonate, which easily leads to uneven mixing, a problem particularly prominent in industrial-scale production.
[0006] Therefore, to solve the problem of uneven mixing, the two powder materials cannot be directly mixed in a dry state; to solve the problem of material re-separation during the drying process, the mixed liquid needs to have a certain viscosity to reduce the sedimentation of the powder materials; to solve the problem of low product performance caused by improper sintering process, the reaction thermodynamics and kinetic parameters of titanium-based lithium ion sieve synthesis need to be matched by optimizing the calcination temperature and calcination time.
[0007] In view of this, the present invention is hereby proposed. Summary of the Invention
[0008] One of the objectives of this invention is to provide a method for preparing a titanium-based lithium-ion sieve, which solves the problems of uneven mixing and material re-separation during the drying process in the prior art; and solves the problem of low product performance caused by improper sintering process.
[0009] The second objective of this invention is to provide a titanium-based lithium ion sieve prepared by the above method, which has a very small and uniform particle size and a high adsorption capacity.
[0010] A third objective of this invention is the application of the aforementioned titanium-based lithium ion sieve in the selective identification and / or extraction of lithium ions from brine. The aforementioned titanium-based lithium ion sieve exhibits extremely high selectivity for lithium ions, enabling it to selectively extract lithium ions from brine, while showing virtually no adsorption of potassium, sodium, magnesium, or calcium ions.
[0011] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a method for preparing a titanium-based lithium-ion sieve, the method comprising the following steps: (1) Mix water-soluble lithium source, titanium source and thickener, and then ball mill and sand mill in sequence to obtain a mixed slurry of lithium source and titanium source; (2) The mixed slurry obtained in step (1) is dried and then crushed to obtain the material to be calcined; (3) The material to be calcined in step (2) is calcined at high temperature using a segmented method and then crushed to obtain a titanium-based lithium ion sieve; The high-temperature calcination temperature range is divided into four zones: a heating zone, a high-temperature reaction zone, a medium-temperature reaction zone, and a cooling zone. The heating zone is set to a temperature of 100–750°C (e.g., 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, etc.), and the high-temperature reaction zone is set to a temperature of 950–1050°C (e.g., 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, etc.). The temperatures can be 950℃, 980℃, 1000℃, 1050℃, etc., the temperature of the intermediate temperature reaction zone is set to 800~900℃ (e.g., 800℃, 820℃, 840℃, 860℃, 880℃, 900℃, etc.), and the temperature of the cooling zone is set to 150~650℃ (e.g., 150℃, 200℃, 250℃, 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃, etc.).
[0012] In step (1) of the present invention, a water-soluble lithium source is used instead of a water-insoluble lithium source (such as lithium carbonate) as the lithium source, and mixed with a titanium source. The water-soluble lithium source will wet and coat the surface of titanium dioxide, which can make the lithium source and titanium source mix more fully, reduce the migration path of lithium ions during the reaction process, and increase the reaction rate.
[0013] In step (3) of the present invention, sintering is carried out in a pusher kiln. The temperature range of the pusher kiln is divided into four zones: heating zone, high temperature reaction zone, medium temperature reaction zone and cooling zone.
[0014] The material will undergo the following reaction in this process: 2C6H5O7Li3+ 3TiO2+ 9O2= 3Li2TiO3+ 5H2O + 12CO2↑ (Or 2Li2C2O4 + 2TiO2 + O2 = 2Li2TiO3 + 4CO2↑) The short residence time in the high-temperature reaction zone is primarily to allow the reactants to nucleate and form a large number of nascent crystal nuclei. These nuclei then move to the medium-temperature reaction zone, where they grow more systematically and completely, thus improving adsorption capacity and selectivity. Optimizing the calcination temperature and time helps match the thermodynamic and kinetic parameters of the titanium-based lithium-ion sieve synthesis, addressing the issue of low product performance caused by improper sintering processes.
[0015] Preferably, in step (1), the mass ratio of the water-soluble lithium source, titanium source and thickener is (1~5):(1~5):(0.01~0.05); The first "1~5" can be, for example, 1, 2, 3, 4, 5, etc. The second "1~5" can be, for example, 1, 2, 3, 4, 5, etc. Among them, "0.01~0.05" can be, for example, 0.01, 0.02, 0.03, 0.04, 0.05, etc.
[0016] Preferably, the water-soluble lithium source is a lithium citrate solution and / or a lithium oxalate solution.
[0017] Preferably, the water-soluble lithium source is prepared by the following method: adding lithium hydroxide to water while stirring, then adding acid, and stirring to obtain a water-soluble lithium source solution.
[0018] Preferably, the mass ratio of water, lithium hydroxide, and acid is (3~5):(1.5~2):(3.5~4.5); Among them, "3~5" can be, for example, 3, 3.5, 4, 4.5, 5, etc.; Among them, "1.5~2" can be, for example, 1.5, 1.6, 1.7, 1.8, 1.9, 2, etc.; Among them, "3.5~4.5" can be, for example, 3.5, 3.6, 3.8, 4, 4.2, 4.5, etc.
[0019] Preferably, the acid includes citric acid and / or oxalic acid.
[0020] More specifically, the water-soluble lithium source is prepared by the following method: ① Preparation of lithium citrate solution: Add deionized water to a stirring device, and while stirring, add lithium hydroxide powder, followed by citric acid powder. Stir at a speed of 100-600 rpm (e.g., 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, etc.) for 1-3 h (e.g., 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.) to obtain a lithium citrate solution. The reaction equation for this process is: C6H8O7 + 3LiOH = C6H5O7Li3 + 3H2O. ② Preparation of lithium oxalate solution: Deionized water is added to a stirring apparatus. While stirring, lithium hydroxide powder is added, followed by oxalic acid dihydrate powder. The mixture is stirred at 100-600 rpm (e.g., 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, etc.) for 1-3 h (e.g., 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.) to obtain a lithium oxalate solution. The reaction equation for this process is: H₂C₂O₄ 2H2O + 2LiOH = Li2C2O4+ 4H2O; Preferably, in step (1), the titanium source includes rutile titanium dioxide and / or anatase titanium dioxide.
[0021] Preferably, in step (1), the particle size of the titanium source is 50~500 nm, for example, it can be 50 nm, 60 nm, 80 nm, 100 nm, 120 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, etc.
[0022] In step (1) of the present invention, rutile titanium dioxide (or anatase titanium dioxide) with a particle size of nanometers is preferred. It is easy to agglomerate in aqueous solution. By ball milling followed by sand milling in aqueous system, the agglomerated titanium dioxide is ground and dispersed, so that the titanium dioxide particles can come into more sufficient contact with the water-soluble lithium source. At the same time, the two materials can be mixed more evenly, which is beneficial to the uniformity of product performance.
[0023] Preferably, in step (1), the tackifier includes any one or a combination of at least two of polyethylene glycol, povidone, polyvinyl alcohol or hydroxyethyl cellulose, preferably polyethylene glycol.
[0024] Preferably, the number average molecular weight of the polyethylene glycol is 200-800, for example, it can be 200, 300, 400, 500, 600, 700, 800, etc., and is more preferably 400-600.
[0025] In step (1) of the present invention, polyethylene glycol is preferably used as a thickener, and PEG-400 (or PEG-600) is even more preferred. This is because, compared with other types of thickeners, it not only increases the viscosity of the liquid, which helps to prevent titanium dioxide from settling in the aqueous solution, but also helps the water-soluble lithium source and titanium source to be uniformly dispersed without stratification during microwave drying; it can also keep the viscosity of the liquid within an appropriate range of 200-500 mPas, so as not to cause difficulties in ball milling and sand milling due to excessive viscosity.
[0026] Preferably, in step (1), the mixing speed of the lithium source, titanium source and thickener is 100~600 rpm (for example, it can be 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, etc.), and the mixing time is 2~4 h, for example, it can be 2 h, 2.5 h, 3 h, 3.5 h, 4 h, etc.
[0027] Preferably, in step (1), the ball milling uses zirconia balls with a diameter of 2-8 mm (e.g., 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm), the ball milling speed is 30-90 rpm (e.g., 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, 90 rpm, etc.), and the ball milling time is 3-5 h, e.g., 3 h, 3.5 h, 4 h, 4.5 h, 5 h, etc.
[0028] Preferably, in step (1), after ball milling, the slurry needs to be fed into the sand mill in one direction at a feed rate of 10~20 L / min (for example, it can be 10 L / min, 12 L / min, 14 L / min, 16 L / min, 18 L / min, 20 L / min, etc.) for grinding.
[0029] Preferably, in step (1), the rotation speed of the sand mill is 500~1000 rpm (for example, it can be 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, etc.), and the number of sand milling cycles is 5-10 times, for example, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, etc.
[0030] Preferably, in step (2), the drying is microwave drying.
[0031] In step (2) of this invention, microwave drying is chosen because using a microwave dryer to dry liquid materials can prevent the water-soluble lithium source solution and titanium dioxide from stratification or sedimentation due to excessive drying time, ensuring uniform dispersion of materials and improving drying efficiency.
[0032] Preferably, in step (2), the feed rate of the mixed slurry is 80-100 kg / h, for example, it can be 80 kg / h, 85 kg / h, 90 kg / h, 95 kg / h, 100 kg / h, etc.
[0033] Preferably, in step (2), the power of the microwave drying is 100~200 kW, for example, it can be 100 kW, 120 kW, 140 kW, 160 kW, 180 kW, 200 kW, etc.; the microwave drying time is 0.5~1 h, for example, it can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1 h, etc.
[0034] Preferably, in step (2), the moisture content of the material to be calcined is 0.1~0.5%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc.
[0035] Preferably, in step (2), the pulverized material needs to be sieved, preferably through a 50-100 mesh sieve (50 mesh, 60 mesh, 70 mesh, 80 mesh, 90 mesh, 100 mesh).
[0036] Preferably, in step (3), the titanium-based lithium ion sieve is obtained by high-temperature calcination in a pusher kiln followed by pulverization.
[0037] Preferably, in step (3), the total length of the pusher kiln is 28~42 m, for example, it can be 28 m, 30 m, 32 m, 34 m, 36 m, 38 m, 40 m, 42 m, etc.
[0038] Preferably, in step (3), the heating zone is divided into 5 sections, each section being 2-3 m long (e.g., 2 m, 2.2 m, 2.4 m, 2.5 m, 2.6 m, 2.8 m, 3 m, etc.). The temperatures of the 5 heating zones are set sequentially as 100-150℃, 250-300℃, 400-450℃, 550-600℃, and 700-750℃. The total residence time of the material in the heating zone is 4-5 h (e.g., 4 h, 4.2 h, 4.6 h, 4.8 h, 5 h, etc.).
[0039] Preferably, in step (3), the high-temperature reaction zone is a single section with a length of 2-3 m (e.g., 2 m, 2.2 m, 2.4 m, 2.5 m, 2.6 m, 2.8 m, 3 m, etc.), the temperature of the high-temperature reaction zone is set to 950-1050℃, and the residence time of the material in the high-temperature reaction zone is 0.8-1 h (e.g., 0.8 h, 0.85 h, 0.9 h, 0.95 h, 1 h, etc.).
[0040] Preferably, in step (3), the intermediate temperature reaction zone is divided into 4 sections, each section being 2-3 m long (e.g., 2 m, 2.2 m, 2.4 m, 2.5 m, 2.6 m, 2.8 m, 3 m, etc.). The temperatures of the 4 intermediate temperature reaction zones are set to 800-900℃, 800-900℃, 800-900℃, and 800-900℃ respectively. The residence time of the material in the intermediate temperature reaction zone is 3.2-4 h (e.g., 3.2 h, 3.4 h, 3.6 h, 3.8 h, 4 h, etc.).
[0041] Preferably, in step (3), the cooling zone is divided into 4 sections, each section being 2-3 m long (e.g., 2 m, 2.2 m, 2.4 m, 2.5 m, 2.6 m, 2.8 m, 3 m, etc.). The temperatures of the 4 cooling zones are set to 600-650℃, 450-500℃, 300-350℃, and 150-200℃ respectively. The residence time of the material in the cooling zone is 3.2-4 h (e.g., 3.2 h, 3.4 h, 3.6 h, 3.8 h, 4 h, etc.).
[0042] In this invention, the temperature range of the pusher kiln is further set through the above-mentioned preferred settings, specifically as follows: Figure 1 As shown, the reaction thermodynamics and kinetic parameters of titanium-based lithium ion sieve synthesis were matched by optimizing the calcination temperature and calcination time, with nucleation occurring in the high-temperature region and nucleus growth and crystal form improvement occurring in the medium-temperature region.
[0043] After the material is preheated in the first five heating zones, it enters the high-temperature zone. During the reaction between the lithium source and the titanium source, lithium ions migrate from the lithium source into the titanium dioxide crystal. From the perspective of reaction thermodynamics, the reaction energy (activation energy) required for lithium ions to initially intercalate and occupy sites on the titanium dioxide crystal is relatively large. The higher the temperature, the more favorable it is for lithium ions to form a nascent transition state structure with titanium dioxide. The explosive formation of a large number of nascent transition state structures is conducive to the formation of more lithium intercalation sites, thereby increasing the adsorption capacity of the synthesized titanium-based lithium ion sieve. The material should not stay in the high-temperature zone for too long, otherwise it may easily lead to the formation of excessively large crystals at high temperatures, reducing the adsorption capacity.
[0044] Subsequently, the material enters the four-stage intermediate-temperature reaction zone. The reaction in this zone primarily involves the secondary growth of the transitional structure formed in the high-temperature zone and crystal refinement. From a reaction kinetics perspective, this secondary growth and crystal refinement require lower temperatures and longer times. Lower temperatures facilitate independent growth and refinement of the crystals at suitable energy levels, rather than agglomerated growth and refinement at high temperatures and energy. Longer times allow lithium ions within the crystals to migrate deeply within the titanium dioxide, forming a perfect crystal structure and improving the selectivity of the titanium-based lithium-ion sieve. Optimizing the calcination temperature and time helps match the reaction thermodynamics and kinetics parameters for the synthesis of titanium-based lithium-ion sieves, addressing the issue of low product performance caused by improper sintering processes.
[0045] Preferably, in step (3), the pulverized material needs to be sieved, preferably through a sieve of 100-200 mesh (e.g., 100 mesh, 120 mesh, 150 mesh, 180 mesh, 200 mesh, etc.).
[0046] In a second aspect, the present invention provides a titanium-based lithium ion sieve, which is prepared by the preparation method of the titanium-based lithium ion sieve as described in the first aspect.
[0047] The titanium-based lithium-ion sieve prepared by the titanium preparation method described in the first aspect has the following crystal form: β -Li2TiO3 crystal form: The titanium-based lithium ion sieve synthesized in this process has a single crystal form and no other impurities.
[0048] Thirdly, the present invention provides an application of the titanium-based lithium ion sieve as described in the second aspect in the selective identification and / or extraction of lithium ions in brine.
[0049] Compared with the prior art, the present invention has the following beneficial effects: (1) In this invention, a water-soluble lithium source is used instead of water-insoluble lithium carbonate as the lithium source, and mixed with water-insoluble titanium dioxide. The water-soluble lithium citrate will be impregnated and coated on the surface of titanium dioxide, which can make the lithium source and titanium source mix more fully, reduce the migration path of lithium ions during the reaction process, and increase the reaction rate. (2) By selecting rutile titanium dioxide (or anatase titanium dioxide) with a nano-sized particle size, it is easy to agglomerate in aqueous solution. By ball milling followed by sand milling in aqueous system, the agglomerated titanium dioxide is ground and dispersed, so that the titanium dioxide particles can come into more sufficient contact with water-soluble lithium citrate. At the same time, the two materials can be mixed more evenly, which is beneficial to the uniformity of product performance. (3) By adding a thickener, the viscosity of the liquid is increased, which helps to prevent titanium dioxide from settling in the aqueous solution and helps lithium citrate and titanium dioxide to be uniformly dispersed without stratification during microwave drying. (4) The present invention uses a microwave dryer to dry liquid materials, which can prevent the lithium citrate solution and titanium dioxide from stratification or sedimentation due to excessive drying time, ensuring uniform dispersion of materials and improving drying efficiency. (5) This invention uses a pusher kiln for sintering. The temperature range of the pusher kiln is divided into four zones: a heating zone, a high-temperature reaction zone, a medium-temperature reaction zone, and a cooling zone. The residence time in the high-temperature reaction zone is short, mainly to allow the reactants to react and nucleate in the high-temperature zone, resulting in a large number of nascent crystal nuclei. Then, the material enters the medium-temperature reaction zone, allowing these crystal nuclei to grow more regularly and completely, which is beneficial to improving adsorption capacity and selectivity. The thermodynamic and kinetic parameters of the reaction in the synthesis of titanium-based lithium ion sieves are matched by optimizing the calcination temperature and calcination time, thus solving the problem of low product performance caused by improper sintering process. Attached Figure Description
[0050] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0051] Figure 1 The diagram shows the temperature zone layout and temperature setting of the pusher kiln provided by this invention.
[0052] Figure 2 SEM image of the titanium-based lithium-ion sieve prepared in Example 1.
[0053] Figure 3 The XRD pattern of the titanium-based lithium-ion sieve prepared in Example 1 is shown.
[0054] Figure 4 The adsorption capacity curves of the titanium-based lithium ion sieve provided in Example 1 at different time points during the calcination process are shown.
[0055] Figure 5 SEM image of the titanium-based lithium-ion sieve prepared in Example 2.
[0056] Figure 6 The image shows the XRD pattern of the titanium-based lithium-ion sieve prepared in Example 2.
[0057] Figure 7 The adsorption capacity curves of the titanium-based lithium ion sieve provided in Example 2 at different time points during the calcination process are shown.
[0058] Figure 8 SEM image of the titanium-based lithium-ion sieve prepared in Example 2.
[0059] Figure 9 The image shows the XRD pattern of the titanium-based lithium-ion sieve prepared in Example 2.
[0060] Figure 10 The adsorption capacity curves of the titanium-based lithium ion sieve provided in Example 2 at different time points during the calcination process are shown. Detailed Implementation
[0061] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.
[0062] Generally, the nomenclature and techniques used in cell and tissue culture, molecular biology, immunology, microbiology, genetics, and protein and nucleic acid chemistry and hybridization, together with those described herein, are those well-known and commonly used in the art. Unless otherwise stated, the methods and techniques of the present invention are generally carried out according to conventional methods well-known in the art and described in various general and more specific references, which are cited and discussed throughout this specification. Enzymatic reactions and purification techniques are carried out according to the manufacturer's instructions, as commonly practiced in the art, or as described herein. The nomenclature, laboratory procedures, and techniques used in analytical chemistry, synthetic organic chemistry, and medical and medicinal chemistry, together with those described herein, are those well-known and commonly used in the art.
[0063] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0064] The present invention will be further illustrated by the following examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.
[0065] Example 1 This embodiment provides a method for preparing a titanium-based lithium-ion sieve, which includes the following steps: (1) Add 350 kg of deionized water to a mixing tank and, while stirring, add 140 kg of lithium hydroxide powder and then add 380 kg of citric acid powder. Stir at 100 rpm for 1 h to obtain a lithium citrate solution. 5 kg of PEG-400 and 240 kg of rutile titanium dioxide powder (particle size 50 nm) were added to a lithium citrate solution and stirred at 100 rpm for 2 h to obtain a slurry with a viscosity of 200 mPas. The slurry was then transferred to a ball mill and ball-milled at 30 rpm for 3 h using 2 mm diameter zirconium dioxide balls as grinding media. The slurry was then fed unidirectionally into a sand mill and ground at 500 rpm with a feed rate of 10 L / min. The discharge from the sand mill was loaded into another mixing tank. The sand milling was repeated 5 times to obtain a mixed slurry of lithium source and titanium source. (2) The above-mentioned mixed slurry of lithium source and titanium source is fed into the conveyor belt of microwave dryer (power of 150 kW). The drying time of the mixed slurry in microwave dryer is 0.5 h, the feed rate of the mixed slurry is 80 kg / h, and the moisture content of the dry block material after microwave drying is 0.1%. Then the dry block material is crushed in a pulverizer and passed through a 50-mesh sieve to obtain the dry powder material to be calcined. (3) The dry powder material to be calcined is placed in a mullite crucible, 3 kg per crucible, and then placed into a pusher kiln for high-temperature calcination. The total length of the pusher kiln is 35 m, and the temperature range of the pusher kiln is divided into four zones: heating zone, high-temperature reaction zone, medium-temperature reaction zone, and cooling zone. The heating zone is divided into 5 sections, each 2.5 m long, with temperature settings of 100℃, 250℃, 400℃, 550℃, and 700℃ respectively. The total residence time of the material in the heating zone is 4 hours. Next, the material enters the high-temperature reaction zone, which has only one section, 2.5 m long, with a temperature setting of 950℃. The residence time of the material in this high-temperature zone is 0.8 hours. Following this, the material enters the medium-temperature reaction zone, which is divided into 4 sections, each 2.5 m long, with temperature settings of 800℃, 800℃, 800℃, and 800℃ respectively. The total residence time of the material in this medium-temperature reaction zone is 3.2 hours. Finally, the material enters the cooling zone, which has 4 sections, each 2.5 m long, with temperature settings of 600℃, 450℃, 300℃, and 150℃ respectively. The total residence time of the material in this medium-temperature reaction zone is 3.2 hours. Finally, the calcined material is placed in a pulverizer for crushing and passed through a 100-mesh sieve to obtain titanium-based lithium ion sieve powder.
[0066] Figure 2 Here is a SEM image of the titanium-based lithium-ion sieve prepared in Example 1. Figure 2 It can be seen that the titanium-based lithium ion sieve prepared in Example 1 has a particle size of 100-300 nm, which is very small and uniform, which is beneficial to improving the adsorption capacity of the titanium-based lithium ion sieve.
[0067] Figure 3 The XRD pattern of the titanium-based lithium-ion sieve prepared in Example 1 is shown below. Figure 3 It can be seen that the crystal form of titanium-based lithium-ion sieves is... β -Li2TiO3 crystal form, proving that the titanium-based lithium ion sieve prepared in Example 1 has a single crystal form and no other impurities.
[0068] Figure 4 The graph shows the adsorption capacity curves of the titanium-based lithium ion sieve provided in Example 1 at different time points during the calcination process. In the continuous production process, samples of the titanium-based lithium ion sieve were taken every 5 hours and acidified with hydrochloric acid to obtain... β -H2TiO3, utilizingβ The adsorption capacity of titanium-based lithium ion sieves was tested using -H2TiO3, by... Figure 4 It can be seen that the titanium-based lithium ion sieve product prepared in Example 1 has uniform performance and an average saturated adsorption capacity of 55 mg / g, which is characterized by a large adsorption capacity.
[0069] Example 2 This embodiment provides a method for preparing a titanium-based lithium-ion sieve, which includes the following steps: (1) Add 400 kg of deionized water to a mixing tank and, while stirring, add 180 kg of lithium hydroxide powder and then add 420 kg of citric acid powder. Stir at 600 rpm for 3 h to obtain a lithium citrate solution. 10 kg of PEG-600 and 280 kg of anatase titanium dioxide powder (particle size 500 nm) were added to a lithium citrate solution and stirred at 600 rpm for 4 h to obtain a slurry with a viscosity of 400 mPas. The slurry was then transferred to a ball mill and ball-milled at 90 rpm for 5 h using 8 mm diameter zirconium dioxide balls as grinding media. The slurry was then fed unidirectionally into a sand mill and ground at 1000 rpm with a feed rate of 20 L / min. The discharge from the sand mill was loaded into another mixing tank. The sand mill was milled 10 times to obtain a mixed slurry of lithium source and titanium source. (2) The above-mentioned mixed slurry of lithium source and titanium source is fed into the conveyor belt of microwave dryer (power of 150 kW). The drying time of the mixed slurry in microwave dryer is 1 h, the feed rate of the mixed slurry is 100 kg / h, and the moisture content of the dry block material after microwave drying is 0.5%. Then, the block material after microwave drying is placed in a pulverizer for pulverization and passed through a 100-mesh sieve to obtain the dry powder material to be calcined. (3) The dry powder material to be calcined is placed in a mullite crucible, 4 kg per crucible, and then placed into a pusher kiln for high-temperature calcination. The total length of the pusher kiln is 35 m, and the temperature range of the pusher kiln is divided into four zones: heating zone, high-temperature reaction zone, medium-temperature reaction zone, and cooling zone. The heating zone is divided into 5 sections, each 2.5 m long, with temperature settings of 150℃, 300℃, 450℃, 600℃, and 750℃ respectively. The total residence time of the material in the heating zone is 5 hours. Next, the material enters the high-temperature reaction zone, which has only one section, 2.5 m long, with a temperature setting of 1050℃. The residence time of the material in this high-temperature zone is 1 hour. Following this, the material enters the medium-temperature reaction zone, which is divided into 4 sections, each 2.5 m long, with temperature settings of 900℃, 900℃, 900℃, and 900℃ respectively. The total residence time of the material in this medium-temperature reaction zone is 4 hours. Finally, the material enters the cooling zone, which has 4 sections, each 2.5 m long, with temperature settings of 650℃, 500℃, 350℃, and 200℃ respectively. The total residence time of the material in this medium-temperature reaction zone is 4 hours. Finally, the calcined material is crushed in a pulverizer and passed through a 200-mesh sieve to obtain titanium-based lithium ion sieve powder.
[0070] Figure 5 Here is a SEM image of the titanium-based lithium-ion sieve prepared in Example 2. Figure 5 It is known that the titanium-based lithium ion sieve synthesized in this invention has a particle size of 100-300 nm, which is very small and uniform, which is beneficial to improving the adsorption capacity of the titanium-based lithium ion sieve.
[0071] Figure 6 The XRD pattern of the titanium-based lithium-ion sieve prepared in Example 2 is shown below. Figure 6 It can be seen that the crystal form of the titanium-based lithium-ion sieve prepared in Example 2 is... β The presence of the Li2TiO3 crystal form proves that the titanium-based lithium-ion sieve synthesized under the process of this invention has a single crystal form and no other impurities.
[0072] Figure 7 This is a graph showing the adsorption capacity curves of the titanium-based lithium-ion sieve provided in Example 2 at different time points during the calcination process. In the continuous production process, samples of the titanium-based lithium-ion sieve were taken every 5 hours and acidified with hydrochloric acid to obtain... β -H2TiO3, utilizing β The adsorption capacity of titanium-based lithium ion sieves was tested using -H2TiO3, by... Figure 7 It can be seen that the titanium-based lithium ion sieve product prepared in Example 2 has uniform performance, an average saturated adsorption capacity of 56 mg / g, and a large adsorption capacity.
[0073] Example 3 This embodiment provides a method for preparing a titanium-based lithium-ion sieve, which includes the following steps: (1) Add 380 kg of deionized water to a mixing tank and, while stirring, add 160 kg of lithium hydroxide powder and then add 450 kg of oxalic acid dihydrate powder. Stir at 350 rpm for 2 h to obtain a lithium oxalate solution. 7.5 kg of PEG-600 and 260 kg of anatase titanium dioxide powder (particle size 100 nm) were added to a lithium oxalate solution and stirred at 350 rpm for 3 h to obtain a slurry with a viscosity of 300 mPas. The slurry was then transferred to a ball mill and ball-milled at 60 rpm for 4 h using 5 mm diameter zirconium dioxide balls as grinding media. The slurry was then fed unidirectionally into a sand mill and ground at 750 rpm with a feed rate of 15 L / min. The discharge from the sand mill was loaded into another mixing tank. The sand milling was repeated 8 times to obtain a mixed slurry of lithium source and titanium source. (2) The above-mentioned mixed slurry of lithium source and titanium source is fed into the conveyor belt of microwave dryer (power of 150 kW). The drying time of the mixed slurry in microwave dryer is 0.75 h, the feed rate of the mixed slurry is 90 kg / h, and the moisture content of the dry block material after microwave drying is 0.3%. Then, the block material after microwave drying is placed in a pulverizer for pulverization and passed through an 80-mesh sieve to obtain the dry powder material to be calcined. (3) The dry powder material to be calcined is placed in a mullite crucible, 3.5 kg per crucible, and then placed into a pusher kiln for high-temperature calcination. The pusher kiln is 35 m long and its temperature range is divided into four zones: heating zone, high-temperature reaction zone, medium-temperature reaction zone, and cooling zone. The heating zone is divided into 5 sections, each 2.5 m long, with temperature settings of 125℃, 275℃, 425℃, 575℃, and 725℃ respectively. The total residence time of the material in the heating zone is 4.5 h. Next, the material enters the high-temperature reaction zone, which has only one section, 2.5 m long, with a temperature set at 1000℃. The residence time of the material in this high-temperature zone is 0.9 h. Following this, the material enters the medium-temperature reaction zone, which is divided into 4 sections, each 2.5 m long, with temperature settings of 850℃, 850℃, 850℃, and 850℃ respectively. The total residence time of the material in this medium-temperature reaction zone is 3.6 h. Finally, the material enters the cooling zone, which has 4 sections, each 2.5 m long, with temperature settings of 625℃, 475℃, 325℃, and 175℃ respectively. The total residence time of the material in this medium-temperature reaction zone is 3.6 h. Finally, the calcined material is crushed in a pulverizer and passed through a 150-mesh sieve to obtain titanium-based lithium ion sieve powder.
[0074] Figure 8 Here is a SEM image of the titanium-based lithium-ion sieve prepared in Example 3. Figure 8 It can be seen that the titanium-based lithium ion sieve prepared in Example 3 has a particle size of 100-300 nm, which is very small and uniform, which is beneficial to improving the adsorption capacity of the titanium-based lithium ion sieve.
[0075] Figure 9 The XRD pattern of the titanium-based lithium-ion sieve prepared in Example 3 is shown below. Figure 9 It can be seen that the crystal form of the titanium-based lithium-ion sieve prepared in Example 3 is... β The presence of the Li2TiO3 crystal form proves that the titanium-based lithium-ion sieve synthesized under the process of this invention has a single crystal form and no other impurities.
[0076] Figure 10 This is a graph showing the adsorption capacity curves of the titanium-based lithium ion sieve provided in Example 3 at different time points during the calcination process. In the continuous production process, samples of the titanium-based lithium ion sieve were taken every 5 hours and acidified with hydrochloric acid to obtain... β -H2TiO3, utilizing β The adsorption capacity of titanium-based lithium ion sieves was tested using -H2TiO3, by... Figure 10 It can be seen that the titanium-based lithium ion sieve product prepared in Example 3 has uniform performance, an average saturated adsorption capacity of 56 mg / g, and a large adsorption capacity.
[0077] Example 4 This embodiment provides a method for preparing a titanium-based lithium ion sieve. The only difference from Example 1 is that the titanium source in step (1) is replaced with an equal mass of metatitanic acid with a particle size D50 of 1.2 μm. The other steps are exactly the same as in Example 1.
[0078] Example 5 This embodiment provides a method for preparing a titanium-based lithium ion sieve. The only difference from Example 1 is that the thickener in step (1) is replaced with an equal mass of PEG-200. The other steps are exactly the same as in Example 1. Step (1) yields a liquid with a viscosity of 100 mPas.
[0079] Example 6 This embodiment provides a method for preparing a titanium-based lithium ion sieve. The only difference from Example 1 is that the thickener in step (1) is replaced with an equal mass of PEG-800. Step (1) yields a liquid with a viscosity of 550 mPas. The other steps are exactly the same as in Example 1.
[0080] Example 7 This embodiment provides a method for preparing a titanium-based lithium ion sieve. The only difference from Embodiment 1 is that the thickener in step (1) is replaced with an equal mass of PVA-400. The other steps are exactly the same as in Embodiment 1.
[0081] Example 8 This embodiment provides a method for preparing a titanium-based lithium-ion sieve. The only difference from Embodiment 1 is that the feed rate of the mixed slurry is 60 kg / h, the drying time is 1.5 h, and the other steps are exactly the same as in Embodiment 1. The moisture content of the material to be calcined is 0.1%.
[0082] Example 9 This embodiment provides a method for preparing a titanium-based lithium-ion sieve. The only difference from Embodiment 1 is that the feed rate of the mixed slurry is 120 kg / h and the drying time is 0.4 h. The other steps are exactly the same as in Embodiment 1, and the moisture content of the material to be calcined is 7%.
[0083] Example 10 This embodiment provides a method for preparing a titanium-based lithium-ion sieve. The only difference from Embodiment 1 is that the temperatures of the five heating zones are set to 160°C, 320°C, 460°C, 620°C, and 760°C, respectively. The other steps are exactly the same as in Embodiment 1.
[0084] Example 11 This embodiment provides a method for preparing a titanium-based lithium-ion sieve. The only difference from Embodiment 1 is that the temperature settings of the five heating zones are 80℃, 200℃, 350℃, 500℃, and 650℃, respectively. The other steps are exactly the same as in Embodiment 1.
[0085] Example 12 This embodiment provides a method for preparing a titanium-based lithium ion sieve. The only difference from Embodiment 1 is that the heating zone is divided into four sections, with the temperature settings for the four sections being 100℃, 300℃, 500℃, and 700℃, respectively. The other steps are exactly the same as in Embodiment 1.
[0086] Example 13 This embodiment provides a method for preparing a titanium-based lithium-ion sieve. The only difference from Embodiment 1 is that the intermediate-temperature reaction zone is divided into three stages, with the temperatures of the three stages set at 850°C, 850°C, and 850°C, respectively. The other steps are exactly the same as in Embodiment 1.
[0087] Example 14 This embodiment provides a method for preparing a titanium-based lithium-ion sieve. The only difference from Embodiment 1 is that the temperature settings of the four cooling zones are 660℃, 520℃, 360℃, and 220℃, respectively. The other steps are exactly the same as in Embodiment 1.
[0088] Example 15 This embodiment provides a method for preparing a titanium-based lithium-ion sieve. The only difference from Embodiment 1 is that the temperature settings of the four cooling zones are 580℃, 420℃, 280℃, and 120℃, respectively. The other steps are exactly the same as in Embodiment 1.
[0089] Example 16 This embodiment provides a method for preparing a titanium-based lithium ion sieve. The only difference from Embodiment 1 is that the cooling section is divided into three stages, with the temperatures of the three stages set at 600℃, 400℃, and 200℃, respectively. The other steps are exactly the same as in Embodiment 1.
[0090] Comparative Example 1 This comparative example provides a method for preparing a titanium-based lithium ion sieve. The only difference from Example 1 is that in step (1), the lithium citrate solution is replaced with 215.8 kg of lithium carbonate powder during mixing. The other steps are exactly the same as in Example 1.
[0091] Comparative Example 2 This comparative example provides a method for preparing a titanium-based lithium ion sieve. The only difference from Example 1 is that PEG-400 is not added during mixing in step (1). The other steps are exactly the same as in Example 1.
[0092] Comparative Example 3 This comparative example provides a method for preparing a titanium-based lithium ion sieve. The only difference from Example 1 is that in step (1), the ball milling time in the ball mill is extended to 5 h, and sand milling is no longer performed. The other steps are exactly the same as in Example 1.
[0093] Comparative Example 4 This comparative example provides a method for preparing a titanium-based lithium ion sieve. The only difference from Example 1 is that in step (2), instead of using a microwave dryer, the material is dried in an oven at 200°C for 24 hours. The moisture content of the dried block material is 3%. The other steps are exactly the same as in Example 1.
[0094] Comparative Example 5 This comparative example provides a method for preparing a titanium-based lithium-ion sieve. The only difference from Example 1 is that after the high-temperature reaction, the intermediate-temperature reaction is not carried out, but the material directly enters the cooling zone, and the residence time of the material in the high-temperature zone is extended. Specifically, the high-temperature reaction zone has only one section, which is 2.5 m long. The temperature of this high-temperature section is set to 950°C, and the residence time of the material in the high-temperature zone is 4 h. The other steps are exactly the same as in Example 1.
[0095] Comparative Example 6 This comparative example provides a method for preparing a titanium-based lithium-ion sieve. The only difference from Example 1 is that a high-temperature reaction is no longer performed. Instead, a medium-temperature reaction is directly carried out after heating, and the temperature of the medium-temperature zone is appropriately increased and the residence time of the material in the medium-temperature zone is extended. Specifically, the medium-temperature reaction zone is divided into 4 sections, each 2.5 m long. The temperatures of the 4 sections are set to 850°C, 850°C, 850°C, and 850°C, respectively. The residence time of the material in the medium-temperature reaction zone is 4 h. The other steps are exactly the same as in Example 1.
[0096] Comparative Example 7 This comparative example provides a method for preparing a titanium-based lithium-ion sieve. The only difference from Example 1 is that instead of using a pusher kiln for high-temperature calcination followed by pulverization, it is directly replaced by a one-stage calcination at 800°C for 12 hours. The other steps are exactly the same as in Example 1.
[0097] Test Example 1 Adsorption capacity test Test samples: finished titanium-based lithium ion sieves prepared in Examples 1-16 and finished titanium-based lithium ion sieves prepared in Comparative Examples 1-7; The test method is as follows: 2 g of titanium-based lithium ion sieve agent is placed in 1000 mL of real brine with a lithium ion concentration of 280.52 mg / L, shaken for 10 h, and the lithium ion concentration in the solution before and after adsorption is determined by ICP, and the adsorption capacity is calculated. The specific test results are shown in Table 1 below: Table 1
[0098] As can be seen from the test results in Table 1, the titanium-based lithium ion sieve product obtained by the optimal process route of the present invention has uniform performance, with an average adsorption capacity of over 55 mg / g, and is characterized by a large adsorption capacity.
[0099] As can be seen from the comparison between Examples 1 and 4, the preferred titanium source of the present invention is nano-sized titanium dioxide. The titanium-based lithium ion sieve prepared from nano-sized titanium dioxide has a smaller particle size than micron-sized metatitanic acid, which allows the titanium dioxide particles to come into more thorough contact with the water-soluble lithium source. At the same time, it can also make the two materials mix more evenly, which is more conducive to the formation of more lithium intercalation sites, resulting in a significant increase in the average adsorption capacity of the product.
[0100] As can be seen from the comparison between Examples 1 and Examples 5-6, the molecular weight of polyethylene glycol is preferably 400-600, with a large average adsorption capacity. However, if the molecular weight is too low, the thickening effect is poor. Titanium dioxide will settle in aqueous solution, and the two materials, water-soluble lithium source and titanium source, are easy to separate and disperse evenly during microwave drying. On the other hand, if the molecular weight is too high, the viscosity will be too high, making ball milling and sand milling difficult. It will also lead to insufficient contact between titanium dioxide particles and water-soluble lithium source, resulting in uneven mixing.
[0101] As can be seen from the comparison between Example 1 and Example 7, polyethylene glycol is preferably used as the thickener in this invention. However, when it is replaced with PVA of equal mass or molecular weight, the thickening effect is poor, and its effect of preventing titanium dioxide from settling in aqueous solution is extremely weak.
[0102] As can be seen from the comparison between Examples 1 and Examples 8 and 9, the feed rate of the mixed slurry when entering the microwave dryer should be in the range of 80-100 kg / h. Otherwise, even if the speed is reduced to extend the drying time or the speed is increased to shorten the drying time, the drying will be insufficient and the material will not be evenly dispersed.
[0103] As can be seen from the comparison between Example 1 and Example 12, if the heating zone is only divided into 4 sections, the heating rate is too fast, which is not conducive to the more regular and complete growth of crystal nuclei in the later stage, resulting in a decrease in adsorption capacity.
[0104] As can be seen from the comparison between Example 1 and Example 13, if the medium-temperature reaction zone is only divided into 3 sections, the segment temperature of the medium-temperature reaction zone is not within the range of this application, and irregularities and defects will also appear in the growth of the medium-temperature zone.
[0105] As can be seen from the comparison between Example 1 and Comparative Example 1, lithium carbonate as the lithium source is prone to uneven mixing, which is particularly prominent in industrial and scale-up production. In contrast, the example uses a water-soluble lithium source instead of a water-insoluble lithium source (such as lithium carbonate) to mix with the titanium source. The water-soluble lithium source wets and coats the surface of titanium dioxide, allowing for more thorough mixing of the lithium and titanium sources. This reduces the migration path of lithium ions during the reaction and increases the reaction rate.
[0106] As can be seen from the comparison between Example 1 and Comparative Example 2, if no thickener is added, titanium dioxide will have serious sedimentation problems in aqueous solution. During microwave drying, the two materials, water-soluble lithium source and titanium source, are easy to separate into layers and disperse evenly.
[0107] As can be seen from the comparison between Example 1 and Comparative Example 3, without sand milling, even with extended ball milling time, the agglomerated titanium dioxide cannot be well ground and dispersed, resulting in insufficient contact with the water-soluble lithium source and poor product performance uniformity.
[0108] As can be seen from the comparison between Example 1 and Comparative Example 4, using a microwave dryer to dry liquid materials can prevent the stratification or sedimentation of lithium citrate solution and titanium dioxide due to excessive drying time, ensuring uniform dispersion of materials and improving drying efficiency.
[0109] As can be seen from the comparison of Example 1 and Comparative Examples 5-6, the present invention uses a pusher kiln for sintering. The temperature range of the pusher kiln is divided into four zones: a heating zone, a high-temperature reaction zone, a medium-temperature reaction zone, and a cooling zone. The residence time in the high-temperature reaction zone is short, and each segment is indispensable, thus solving the problem of low product performance caused by improper sintering process.
[0110] Test Example 2 Lithium ion extraction test in brine Test samples: finished titanium-based lithium ion sieves prepared in Examples 1-16 and finished titanium-based lithium ion sieves prepared in Comparative Examples 1-7; The testing method is as follows: The titanium-based lithium ion sieve produced above... β -Li₂TiO₃, after acidification with 0.5 M hydrochloric acid solution, yields β -Li2TiO3, 2 g β -Li2TiO3 was placed in 1 L of real brine for adsorption for 10 h, then the powder was filtered to obtain a filter cake, and then the filter cake was placed in 1 L of 0.5M hydrochloric acid solution for desorption for 3 h to obtain the eluent. The concentration of potassium, sodium, magnesium, calcium and lithium ions in the eluent was sampled and tested. The specific test results are shown in Tables 2 and 3 below: Table 2
[0111] Table 3
[0112] As shown in Tables 2 and 3, the titanium-based lithium ion sieve produced by this invention has extremely high selectivity for lithium ions, enabling it to selectively extract lithium ions from brine. It does not adsorb potassium, sodium, magnesium, or calcium ions, resulting in a very high ratio of lithium ions to sodium, potassium, magnesium, and calcium ions in the eluent. This yields a high-quality lithium extraction eluent, achieving selective extraction of lithium ions from brine.
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a titanium-based lithium-ion sieve, characterized in that, The preparation method of the titanium-based lithium ion sieve includes the following steps: (1) Mix water-soluble lithium source, titanium source and thickener, and then ball mill and sand mill in sequence to obtain a mixed slurry of lithium source and titanium source; (2) The mixed slurry obtained in step (1) is dried and then crushed to obtain the material to be calcined; (3) The material to be calcined in step (2) is calcined at high temperature using a segmented method and then crushed to obtain a titanium-based lithium ion sieve; The high-temperature calcination temperature range is divided into four zones, which include a heating zone, a high-temperature reaction zone, a medium-temperature reaction zone, and a cooling zone; wherein, the temperature of the heating zone is set to 100~750℃, the temperature of the high-temperature reaction zone is set to 950~1050℃, the temperature of the medium-temperature reaction zone is set to 800~900℃, and the temperature of the cooling zone is set to 150~650℃. The heating zone is divided into 5 sections, each 2-3 m long. The temperature settings of the 5 heating zones are 100-150℃, 250-300℃, 400-450℃, 550-600℃, and 700-750℃ respectively. The total residence time of the material in the heating zone is 4-5 h. The high-temperature reaction zone is a single section, 2-3 m in length, with a temperature of 950-1050°C and a residence time of 0.8-1 h for the material. The intermediate temperature reaction zone is divided into 4 sections, each 2-3 m long. The temperatures of the 4 intermediate temperature reaction zones are set at 800-900℃, 800-900℃, 800-900℃, and 800-900℃ respectively. The residence time of the material in the intermediate temperature reaction zone is 3.2-4 h. The cooling zone is divided into 4 sections, each 2-3 m long. The temperatures of the 4 cooling zones are set at 600-650℃, 450-500℃, 300-350℃, and 150-200℃ respectively. The residence time of the material in the cooling zone is 3.2-4 h. The titanium source includes rutile titanium dioxide and / or anatase titanium dioxide; The water-soluble lithium source is a lithium citrate solution and / or a lithium oxalate solution; The thickener is polyethylene glycol; The number-average molecular weight of the polyethylene glycol is 400-600; The drying process is microwave drying.
2. The method for preparing the titanium-based lithium-ion sieve according to claim 1, characterized in that, In step (1), the mass ratio of the water-soluble lithium source, titanium source and thickener is (1~5):(1~5):(0.01~0.05).
3. The method for preparing the titanium-based lithium-ion sieve according to claim 1, characterized in that, The water-soluble lithium source is prepared by the following method: adding lithium hydroxide to water while stirring, then adding acid, and stirring to obtain a water-soluble lithium source solution; The mass ratio of water, lithium hydroxide, and acid is (3~5):(1.5~2):(3.5~4.5); the acid includes citric acid and / or oxalic acid.
4. The method for preparing the titanium-based lithium-ion sieve according to claim 1 or 2, characterized in that, In step (1), the particle size of the titanium source is 50~500 nm.
5. The method for preparing the titanium-based lithium-ion sieve according to claim 1, characterized in that, In step (1), the mixing speed of the lithium source, titanium source and thickener is 100~600 r / min, and the mixing time is 2~4 h.
6. The method for preparing the titanium-based lithium-ion sieve according to claim 1, characterized in that, In step (1), the ball mill uses zirconia balls with a diameter of 2-8 mm, the ball milling speed is 30-90 r / min, and the ball milling time is 3-5 h.
7. The method for preparing the titanium-based lithium-ion sieve according to claim 1, characterized in that, In step (1), after ball milling, the slurry needs to be fed into the sand mill in one direction at a feed rate of 10~20 L / min for grinding.
8. The method for preparing the titanium-based lithium-ion sieve according to claim 1, characterized in that, In step (1), the rotation speed of the sand mill is 500~1000 r / min, and the number of sand milling cycles is 5~10.
9. The method for preparing the titanium-based lithium-ion sieve according to claim 1, characterized in that, In step (2), the feed rate of the mixed slurry into the microwave dryer is 80~100 kg / h.
10. The method for preparing the titanium-based lithium-ion sieve according to claim 1, characterized in that, The microwave drying process uses a power of 100-200 kW and a drying time of 0.5-1 h.
11. The method for preparing the titanium-based lithium-ion sieve according to claim 1, characterized in that, In step (2), the moisture content of the material to be calcined is 0.1~0.5%.
12. The method for preparing the titanium-based lithium-ion sieve according to claim 1, characterized in that, In step (2), the powdered material needs to be sieved.
13. The method for preparing the titanium-based lithium-ion sieve according to claim 12, characterized in that, In step (2), the pulverized material needs to be passed through a 50-100 mesh sieve.
14. The method for preparing the titanium-based lithium-ion sieve according to claim 1, characterized in that, In step (3), the titanium-based lithium ion sieve is obtained by high-temperature calcination in a pusher kiln followed by pulverization.
15. The method for preparing the titanium-based lithium-ion sieve according to claim 14, characterized in that, In step (3), the total length of the pusher kiln is 28~42 m.
16. The method for preparing the titanium-based lithium-ion sieve according to claim 1, characterized in that, In step (3), the powdered material needs to be sieved.
17. The method for preparing the titanium-based lithium-ion sieve according to claim 16, characterized in that, In step (3), the pulverized material needs to be passed through a 100-200 mesh sieve.
18. A titanium-based lithium-ion sieve, characterized in that, The titanium-based lithium ion sieve is prepared by the preparation method of the titanium-based lithium ion sieve as described in any one of claims 1-17.
19. The application of the titanium-based lithium ion sieve as described in claim 18 in the selective identification and / or extraction of lithium ions from brine.
Citation Information
Patent Citations
Lithium ion battery electrode active substance, preparation method and electrode thereof, and battery
CN112736233A
Titanium-based lithium ion exchanger and preparation method thereof
CN114288983A
